THE CONCEPT OF IDENTITY DEPICTED BY MARGO IN JOHN GREEN’S PAPER TOWN - Imam Ramadhan, Teuku; Grace M. Litaay, Adeline (TANDA, 2023)
This study aims to analyze Margo’s Identity in John Green’s Paper Town. The primary source is the novel Paper Town by John Green. To analyze the problems formulated above, the writer uses the theory of identity from Erik Erikson. The result of the study is Margo is an introverted person. She does not like to share her feelings with others. She always keeps her problems to herself. It makes other people create their perspectives about her and she cannot show her real side of her. Margo is also a smart girl. When she is a child, she does an investigation about the dead man. She manipulates the police and the woman in the apartment so she can get information about the dead man. Her decision to leave the town and never want to come back is a big decision. Her parents, sister, friends, and all the people live in that town, but she chooses to leave all of them forever. When she finds out her boyfriend is cheating on her with her best friend, she starts to change her way of thinking. The finding of this thesis is identity is developed by individuals, but must be recognized and confirmed by others. In Paper Towns, those that are idealized are done so in a positive light. If people have a negative outlook on generalized portions of life, then when faced with individual forms, their negative outlook will translate and prevent people from truly being honest about whether something is good or bad for their identity.